2017
DOI: 10.1039/c6ob01585a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of simplified pironetin analogues with modifications in the side chain and the lactone ring

Abstract: The preparation of several new analogues of the natural dihydropyrone pironetin is described. They differ from the natural product mainly in the nature of the side chain and the lactone ring. Their cytotoxic activity has been measured. In addition, their interaction with tubulin, their ability to inhibit the secretion of the vascular endothelial growth factor (VEGF) and the expression of angiogenesis and telomerase-related genes have been determined. Unexpectedly, and unlike pironetin, the lactones studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The pironetin binding site on α-tubulin is considered an unexplored target for cancer therapeutics [ 7 ]. There are a few recent studies dedicated to the design of novel pironetin derivatives, such as phenylpironetin analogs [ 28 , 29 ] and functionalized pironetin analogs [ 25 , 26 , 27 ]. Otherwise, the pironetin scaffold is not frequently used as a template to build anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pironetin binding site on α-tubulin is considered an unexplored target for cancer therapeutics [ 7 ]. There are a few recent studies dedicated to the design of novel pironetin derivatives, such as phenylpironetin analogs [ 28 , 29 ] and functionalized pironetin analogs [ 25 , 26 , 27 ]. Otherwise, the pironetin scaffold is not frequently used as a template to build anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…The unique capacity of PRN to interfere with microtubule assembly via α-tubulin binding, coupled with its antitumor properties, have stimulated the search for more potent analogues. Over the past 20 years, synthetic approaches have been explored to produce PRN via different chemical routes [ 18 , 19 , 20 , 21 , 22 ] and to generate simplified PRN derivatives with improved pharmacological properties and metabolic stability [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Hybrid molecules combining the scaffold of PRN with other MTAs, such as combretastatin and colchicine, have been designed as well [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This pocket is usually in a closed conformation, Pironetin binding opens it with some residues shifting more than 10 Å [56]. The ethyl group of Pironetin seems to play an essential role in its action, due to the biological activity decrease in Pironetin variants where this group has been removed or replaced by other groups [57][58][59][60]. All these facts represent a challenge for binding the xanthanolides into the pironetin binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Qing and co‐workers synthesized gem ‐difluorinated analogue 4 and the corresponding C5‐epimer epi ‐ 4 , and the GI 50 values for these analogues were 600 and 1500 n m against MGC803 and A375 cancer cell lines, respectively . Marco and co‐workers prepared a series of simplified pironetin analogues 5 to evaluate the structure–activity relationships at the C4 and C5 positions . They proposed that the C4 ethyl group is necessary for biological activity, as analogue 5 c had a GI 50 value of 22 μ m , whereas 5 b was inactive with a GI 50 value >200 μ m .…”
Section: Introductionmentioning
confidence: 99%
“…[27] Marco and co-workers prepared as eries of simplified pironetin analogues 5 to evaluate the structure-activity relationshipsa tt he C4 andC 5p ositions. [21,28,29] They proposed that the C4 ethyl group is necessary for biological activity,a sa nalogue 5c had aG I 50 value of 22 mm,w hereas 5b was inactive with aG I 50 value > 200 mm. The group also concluded that the stereochemistry at the C5 position did not significantly influence the biological activity of their analoguesb ecause analogue 5a and epi-5a had GI 50 values of 22.9 and 44 mm,r espectively.W hile Marco and coworkers were able to explore the structure-activity relationship at the C4 andC 5p ositions of the lactone with their simplified scaffold,t heir analogues were all 1000-fold less active than pironetin in their assays.…”
Section: Introductionmentioning
confidence: 99%